Nonendoscopic predictors of large esophageal varices - Ahmed A ElNaggar; Mohamed S Gomaa; May M Fawzy (SpringerOpen, 2012)
Background There is a particular need for noninvasive predictors of esophageal varices (EV) that might help reduce medical, social, and economic costs. Our study aimed at studying the noninvasive predictors of EV. Patients and methods A total of 100 live cirrhotic patients with compensated liver functions were subjected to full clinical, laboratory, and imaging investigations. Results A total of 55% of the studied groups showed EV; 39% showed high-grade EV (grades III, IV, and V). Platelet count and platelet count/splenic diameter ratio have the highest accuracy and specificity for predicting EV, whereas platelet count/splenic diameter ratio has the highest predictive accuracy for the presence of large EV. Conclusion The platelet count/splenic diameter ratio can predict the presence of EV and large-sized EV.